The Regulations of Individuals' Sunna of the Fundamentalists - Al-Samra'i, Mohammad (Journal of Tikrit university for humanities - مجلة جامعة تكريت للعلوم الانسانية; Vol 26 No 6 (2019): Journal of Tikrit University for HumanitiesDO - 10.25130/hum.v26i6.715, 2019)
Praise be to Allah, Lord of the Worlds, and prayers and peace be upon our master Muhammad and his family and companions In my research, I have reached the following: I have reached the conclusion that the singular predicates have rules that must be taken into consideration, and some of these rules are agreed upon by the fundamentalists. I have come to the conclusion that each individual Sunna corresponding to Qura'an and frequent Sunna are valid Sunna, and should be taken by. I have come to the conclusion that Sunna before being recommended must be examined to determine whether it pervades sorrow or not; because the things that pervade sorrow may be a reason to leave the individuals of some fundamentalists. I have found that there is a difference between the fundamentalists in considering the hadith as a proof, which is a section of the individual. I have come to the conclusion that a section of the fundamentalists has not taken into consideration the individuals of hadith at all.